Harnessing the power of RNA therapeutics in treating ischemic heart failure: the TRAIN-HEART story - Albert, Alba M.; Balamurali, Deepak; Beslika, Evangelia; Fernandez, Ileana D.; Genedy, Hussein H.; Babaei Khorzoughi, Reyhaneh; Lauta, Francesca Cecilia; Peppas, Panagiotis; Ragone, Isabella; Rizzari, Giorgia; Sansonetti, Marida; Silva, Joana; et al. (Frontiers in Cardiovascular Medicine, 2024)
Ischemic heart disease (IHD) is one of the world's foremost killers, accounting for 16% of all deaths worldwide. IHD is the main cause of heart failure (HF), as it leads to pathological changes in the heart, improper pumping function and eventual death. Therapeutic interventions usually follow a systemic general strategy for all heart failure subtypes due to the lack of a deep understanding of the disease mechanisms. Hence, HF and IHD therapeutics need groundbreaking concepts to guide the development of a new therapeutics class that tackles the disease at a molecular level. The TRAIN-HEART consortium, a Marie Skłodowska-Curie Actions Innovative Training Network (MSCA-ITN) funded by the European Commission, was established with the goal of filling that gap and developing RNA-based cardiovascular therapeutics. Created in the context of the Horizon 2020 research and innovation program, TRAIN-HEART comprises three key work packages (WPs) focusing on the pathogenesis of heart disease (WP1), the therapeutic potential of RNA therapeutics (WP2), and the development of new efficient delivery systems (WP3). Fifteen international early stage researchers (ESRs) from multiple complementary scientific disciplines were recruited to collaborate with a network of PIs from nine academic and eight non-academic partners in various disciplines to fully harness their collective potential for the betterment of HF treatment. This article provides an overview of the benefits of being part of an MSCA-ITN, with its different training and networking opportunities, maximizing ESRs' potential and broadening collaborative research possibilities. Finally, it describes what was like to do a PhD during the COVID-19 pandemic, with all the uncertainty and concern attached to it. Luckily, TRAIN-HEART stood out as a proactive network, finding new initiatives and alternatives to promote scientific and personal development. By bringing together leading academic teams, (biotech) companies, and highly motivated researchers, TRAIN-HEART is expanding scientific horizons and accelerating future development of effective RNA-based therapies to treat IHD.